512. The relationship of Clostridioides difficile in-vitro antibiotic resistance, prior exposure to antibiotics and ribotype: A single center study. (15th December 2022) - Alsoubani, Majd; Thorpe, Cheleste M; Walk, Seth; McDermott, Laura A; Snydman, David R
Abstract: Background: Antibiotic exposure is the most important risk factor for Clostridioides difficile associated diarrhea (CDAD). Little information has been reported on the relationship between prior antibiotic exposure, antibiotic resistance of C. difficile, and isolate ribotype. Methods: C. difficile isolates were collected from the stools of patients with CDAD. Isolates were ribotyped by PCR-based fragment analysis. Susceptibility testing was performed using Clinical & Laboratory Standards Institute (CLSI) recommended methods. MIC results were interpreted using European Committee on Antimicrobial Susceptibility Testing (EUCAST) epidemiologic cut off values or the CLSI breakpoints. Demographic data and antibiotic exposure in the 30 days period prior to C. difficile isolation were collected via retrospective chart review. Results: Of a total of 490 C. difficile isolates, 335 (67.3%) isolates were resistant to one or more antibiotics (Table 1). Patients who had higher Charlson Comorbidity Score (CCI) and who had hospital associated CDAD were more likely to receive antibiotics (Table 2). Moxifloxacin resistance was significantly associated with prior fluoroquinolone exposure (OR 2.5, CI 95% 1.5-4.1). Fluoroquinolone use was associated with vancomycin resistance (OR 2.7, CI 95% 1.3-5.6) and rifampin resistance (OR 1.9, CI 95% 1.2-3). Infection with a clindamycin resistant isolate was more likely to be hospital acquired (p = 0.006). We identified 54 different ribotypes (Figure 1). Prior treatment with aminopenicillins increased the odds of acquiring ribotype 053-163 (OR 2.9, 95% CI 1.0-8.2) and ribotype 002 (OR 3.2; CI 95% 1.0-10) (Table 3). .Prior treatment with cephalosporins had an increased risk of 014-020 (OR 2.0, CI 95% 1.2-3.3); prior treatment with carbapenems was associated with ribotype 106 (OR 2.3, CI 95% 1.2-4.4). Isolation of ribotype 027 following prior treatment to fluroquinolones was marginally significant (p = 0.054). Conclusion: Specific antibiotic exposure may select for infection by specific C. difficile ribotypes, which can often lead to infection with resistant strains. Prior fluoroquinolone treatment, in particular, was associated with an increased risk of isolating multi-drug resistant strains. Disclosures: Cheleste M. Thorpe, MD, Actelion: Grant/Research Support|Deinove: Advisor/Consultant|General Mills: Grant/Research Support|Merck: Grant/Research Support|Pfizer: Grant/Research Support|Summit: Advisor/Consultant|Summit: Grant/Research Support David R. Snydman, MD, Merck: Advisor/Consultant|Merck and Company: Grant/Research Support|Prolacta: Advisor/Consultant|Prolacta: Grant/Research Support|Seres: Advisor/Consultant|Seres Health: Grant/Research Support|Summit Plc: Grant/Research Support|Takeda: Advisor/Consultant|Takeda: Grant/Research Support|Visterra: Advisor/Consultant.